Analisis Kebijakan Kevin Rudd terkait Pencari Suaka di Australia dalam PNG Solutions - Helmiyana, Nurlaily (Talenta Publisher, 2020)
Papua New Guinea Solution is a bilateral relationship between Australia under Prime Minister Kevin Rudd and Papua New Guinea regarding anti-resettlement conducted by people who want to access Australia and obtain refugee status by boat. This solution was taken after Kevin Rudd who came from the Australian Labor Party sent Pacific Solutions which had been used during Prime Minister Howard's administration. The difference in efforts to overcome the arrival of aid can be seen by using the Bureaucratic Model in its analysis. This effort was carried out with the aim of securing Australia. The problem is that Australia ratified the 1951 Refugees conference. The essence of PNG Solutions is individuals or groups who come to Australia who can pass Australia, and without a visa and a clear identity are not allowed into Australia and will be sent in Papua New Guinea. Australia's national interests can hurt ratified conventions. This study uses a qualitative method using secondary resources, and analysis uses the concept of securitization and uses Barry Buzan's research in his book People, State, and Fear. Then the policy analysis is taken by Prime Minister Rudd by using the Bureaucratic Model due to bargaining in Australia's domestic politics. Keywords: PNG Solutions, Asylum Seeker, Australia’s Foreign Policy